Xanthan gum in drug release - Cortes, Hernán; Caballero-Florán, Isaac H.; Mendoza-Muñoz, Néstor; Escutia-Guadarrama, Lidia; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; González-Del Carmen, Manuel; Varela-Cardoso, Miguel; González-Torres, Maykel; Florán, Benjamín; Del Prado-Audelo, María L.; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2020)
Controlled release is of vital relevance for many drugs; thus, there is a keen interest in materials that can improve the release profiles of formulations administered via buccal, transdermal, ophthalmic, vaginal, and nasal. The desirable effects of those materials include the improvement of stability, adhesiveness, solubility, and retention time. Hence, different synthetic and natural polymers are utilized to achieve these objectives. In this respect, xanthan gum is an anionic polysaccharide that can be obtained from Xanthomonas bacteria. It is a natural polymer broadly employed in numerous food products, lotions, shampoos, and dermatological articles. Furthermore, due to its physicochemical features, xanthan gum is growingly utilized for the development and improvement of drug delivery systems. In this regard, encouraging findings have been revealed by recent formulations for pharmaceutical applications, including antiviral carriers, antibacterial transporters, transdermal patches, vaginal formulations, and anticancer medications. In this article, we perform a concise description of the chemical properties of xanthan gum and its role as a modifier of drug release. Furthermore, we present an outlook of the state of the art of research focused on the utilization of xanthan gum in varied pharmaceutical formulations, which include tablets, films, hydrogels, and nanoformulations. Finally, we discuss some perspectives about the use of xanthan gum in these formulations.